The biogenesis and maintenance of PSII: Recent advances and current challenges - Komenda, Josef; Sobotka, Roman; Nixon, Peter J (The Plant cell, 2024)
The growth of plants, algae, and cyanobacteria relies on the catalytic activity of the oxygen-evolving PSII complex, which uses solar energy to extract electrons from water to feed into the photosynthetic electron transport chain. PSII is proving to be an excellent system to study how large multi-subunit membrane-protein complexes are assembled in the thylakoid membrane and subsequently repaired in response to photooxidative damage. Here we summarize recent developments in understanding the biogenesis of PSII, with an emphasis on recent insights obtained from biochemical and structural analysis of cyanobacterial PSII assembly/repair intermediates. We also discuss how chlorophyll synthesis is synchronized with protein synthesis and suggest a possible role for PSI in PSII assembly. Special attention is paid to unresolved and controversial issues that could be addressed in future research.
Keywords: Thylakoids; Photosynthesis; Photosystem II Protein Complex; Chlorophyll; chlorofyl; tylakoidy; fotosystém II (proteinový komplex); Cyanobacteria; fotosyntéza; sinice